License to Gamble: Discursive Perspectives on the 2019 Reregulation of the Swedish Gambling Market - Goedecke, Klara; Spångberg, Jessika; Svensson, Johan (Critical Gambling Studies, 2023)
During the last decades, several European gambling markets have been reregulated. In 2019, it was Sweden’s turn; the former oligopoly was replaced by a licensing system. In this article, the governmental inquiry in which the new system was proposed, outlined, and justified is studied using discourse analysis. Medical, public health, and free market discourses have been shown to dominate articulations of gambling in several national contexts, but the ways in which these discourses interact, overlap, and differ are crucial to understand better in order to appreciate the production and legitimation of meanings around gambling. Moreover, the 2019 reregulation has not yet been studied from discursive perspectives; thus, the article makes both theoretical and empirical contributions. The article demonstrates that market and medical discourses structure the inquiry. While they sometimes overlap and merge, their co-existence also causes tensions, for instance regarding whether an increase in gambling is acceptable or not. The article points to a strengthening of market and medical discourses and a weakening of public health discussion within Swedish gambling debates.